Arcs of integration: an international study of supply chain strategies - Frohlich, Markham T.; Westbrook, Roy (Journal of Operations Management, 2001)
AbstractThough there is a wide acceptance of the strategic importance of integrating operations with suppliers and customers in supply chains, many questions remain unanswered about how best to characterize supply chain strategies. Is it more important to link with suppliers, customers, or both? Similarly, we know little about the connections between supplier and customer integration and improved operations performance. This paper investigated supplier and customer integration strategies in a global sample of 322 manufacturers. Scales were developed for measuring supply chain integration and five different strategies were identified in the sample. Each of these strategies is characterized by a different “arc of integration”, representing the direction (towards suppliers and/or customers) and degree of integration activity. There was consistent evidence that the widest degree of arc of integration with both suppliers and customers had the strongest association with performance improvement. The implications for our findings on future research and practice in the new millennium are considered.